Unveiling the Synergy: How Entrepreneurial Marketing and Product Quality Drive Purchase Decisions through the Lens of Digital Marketing - Mariana Purnamasari; Aditiya Hermawan; Junaedi (Komunitas Dosen Indonesia, 2024)
This study delves into the complex interactions between entrepreneurial marketing, product quality, and digital marketing within Indonesia's dynamic digital marketplace, aiming to decipher their combined impact on purchase decisions. Employing a quantitative causal approach alongside Structural Equation Modeling (SEM) and Smart PLS software, the research endeavors to uncover the underlying mechanisms driving consumer behavior in this context. Findings indicate that while Entrepreneurial Marketing may not exert a direct influence on purchase decisions, both Product Quality and Digital Marketing play significant roles in shaping consumer choices. Notably, Digital Marketing emerges as a crucial moderating factor, enhancing the effects of Entrepreneurial Marketing and Product Quality on purchase decisions. These results underscore the pivotal role of digital platforms in influencing consumer behavior and preferences. The study provides actionable insights for businesses, advocating for the integration of digital marketing strategies and the promotion of high-quality products to effectively engage online consumers and drive purchasing behavior. While acknowledging limitations such as sample size and generalizability, this research lays the groundwork for future investigations into the nuanced dynamics of digital marketing's impact on marketing strategies and product quality enhancement. Overall, this study contributes to advancing the understanding of digital consumer behavior, emphasizing the transformative potential of digital marketing in today's evolving digital marketplace.